Impact of Soft Tissue Grafts to Reduce Peri-implant Alterations After Immediate Implant Placement and Provisionalization in Compromised Sockets - Frizzera, Fausto; Freitas, Rubens Moreno de; Munoz-Chavez, Oscar Fernando [UNESP]; Cabral, Guilherme; Shibli, Jamil Awad; Marcantonio Jr, Elcio [UNESP] (Quintessence Publishing Co Inc, 2019)
This study evaluated the impact of soft tissue grafts to reduce marginal peri-implant recession (MPR) after 1 year of follow-up. A total of 24 patients with one single failing maxillary incisor presenting facial bone dehiscence and receiving an immediate implant, bone graft, and provisional were randomly divided into three groups (n = 8 in each group): control (CTL), collagen matrix (CM), and connective tissue graft (CTG). Clinical, photographic, and tomographic analyses were performed to evaluate tissue alterations. The use of a CTG avoided MPR (P < .05) and provided better contour of the alveolar ridge (P < .01) and greater thickness (P < .05) of the soft tissue at the implant facial aspect.